Upaya Perlindungan Hukum Terhadap Anak Sebagai Korban Penganiayaan Dalam Rumah Tangga - Jhon Jeffri Simarmata; Tardip Panggabean; M.Wira Utama (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Legal protection for children who are victims of domestic abuse is an issue that requires serious attention in the legal system. Children who experience abuse in the domestic environment are vulnerable to long-term physical, psychological and emotional impacts. This article discusses legal protection efforts that can be taken to protect children who are victims of domestic abuse. This research explores the international and national legal framework that regulates children's rights and their protection, and focuses on legal instruments that can be used to address this problem. Through a normative legal analysis approach, this article outlines various steps that can be taken by relevant institutions and authorities to ensure strong protection for children who are victims of domestic abuse. Some of the recommended steps include increasing public awareness regarding children's rights, strengthening cooperation between child protection agencies, the police, and the justice system, as well as expanding the definition and enforcement of laws related to domestic abuse. This article also reviews challenges that may arise in the implementation of legal protection efforts, including underreporting of cases, stigmatization, and imbalances in access to justice. Therefore, integrating a multidisciplinary approach and providing psychosocial support to child victims is also an important focus in overcoming this problem. By integrating legal, social and psychological perspectives, this paper concludes that legal protection for children who are victims of domestic abuse requires a comprehensive approach involving various stakeholders. Only through concerted efforts to strengthen the legal framework and its implementation, and ensure equitable access to justice, can children be effectively protected from the impacts of abuse in the domestic context.